Autoimmune signals in non‐segmental vitiligo patients are associated with distinct clinical parameters and toxic exposures. (15th June 2012) - Arunachalam, M.; Colucci, R.; Berti, S.; Kline, J.A.; Lotti, T.; Lotti, F.; Dragoni, F.; Moretti, S.
Abstract: Background Although non‐segmental vitiligo is commonly considered an autoimmune disease, the possible differences between non‐segmental vitiligo patients with and without autoimmune signals have not been clearly established. Objective To perform a comparison of non‐segmental vitiligo patients with autoimmune signals (AIS) vs. those without autoimmune signals (NAIS) in regards to clinical characteristics and toxic/drug exposure. Methods 112 vitiligo patients were selected for a sex and age matched (1 : 1) case control study at an university based dermatology outpatient hospital specialized in pigmentary disorders. Medical assessment was performed by dermatologists using the modified Vitiligo European Task Force form and serological and clinical signs of autoimmunity were evaluated. Results Disease duration, age of onset, patient history of cardiovascular disease, past smoking history, use of drugs, and consummation of goitrogenic foods were all significantly increased in the AIS group using McNemar's test for matched pairs. In our conditional regression model, the simultaneous presence of disease duration, use of prescription drugs, and consummation of goitrogenic foods were the best predictors of AIS vitiligo patients. Conclusion The evaluation of non‐segmental vitiligo patients according to the presence vs. the absence of autoimmune signals allows us to correlate patients exhibiting autoimmune phenomenon with certain clinical characteristics, namely long disease duration, use of prescription drugs, and consumption of goitrogenic substances. In the presence of the aforementioned clinical profile, we suggest an evaluation of autoimmune signals.